"Efecto del carbonato de calcio en la asimilación de nutrientes en el cultivo de banano en la zona de valencia los Riós. - Zamora Galarza, Iván Arturo (2014)
In order to determine the effect of the use of calcium carbonate in the assimilation of nutrients in growing banano.se conducted field research design using a randomized complete block with 5 treatments and 4 replications using different doses of carbonate calcium plus a control . The results indicate that no statistical difference was found in all the variables under study, to evaluate treatments consider the following characters : Increase in height between the first and second measurement , height increase in the second measurement , height increase in last measurement , final height , diameter increase plant in the first measurement , the diameter increasing in the second measurement plants , plant diameter increase in the last measurement and the final diameter of plants . Analyzing the results it was concluded that the final plant height values of analysis of variance in which not register statistical significance for treatments coefficient of variation being 6.51% and the highest average final plant height was shown by witness to 204.5 cm, the total increase in diameter of plants in the last measurement statistical significance was determined at the 0.05 level for treatment with a coefficient of variation of 9.62% and according to the Tukey test treatment where the dose was applied to 1350 kg / ha had the highest increase in value of 18.76 cm diameter , not differ statistically from the other treatments and final diameter of the treatment plant stems where the dose was applied 1350kg / I have the highest value was obtained with 51.76 cm without differ statistically from the other treatments (T2 ) , (T1 ) and the control which showed average between 50.91 and 47.46 kg / ha, with lower values on the treatment (T4 ) with 44.68 cm 1800kg/ha CaCO3 increase